An RNA‐seq protocol to identify mRNA expression changes in mouse diaphyseal bone: Applications in mice with bone property altering Lrp5 mutations. (18th September 2013) - Ayturk, Ugur M; Jacobsen, Christina M; Christodoulou, Danos C; Gorham, Joshua; Seidman, Jonathan G; Seidman, Christine E; Robling, Alexander G; Warman, Matthew L
ABSTRACT Loss‐of‐function and certain missense mutations in the Wnt coreceptor low‐density lipoprotein receptor‐related protein 5 (LRP5) significantly decrease or increase bone mass, respectively. These human skeletal phenotypes have been recapitulated in mice harboring Lrp5 knockout and knock‐in mutations. We hypothesized that measuring mRNA expression in diaphyseal bone from mice with Lrp5 wild‐type (Lrp5+/+), knockout (Lrp5–/–), and high bone mass (HBM)‐causing (Lrp5p.A214V/+) knock‐in alleles could identify genes and pathways that regulate or are regulated by LRP5 activity. We performed RNA‐seq on pairs of tibial diaphyseal bones from four 16‐week‐old mice with each of the aforementioned genotypes. We then evaluated different methods for controlling for contaminating nonskeletal tissue (ie, blood, bone marrow, and skeletal muscle) in our data. These methods included predigestion of diaphyseal bone with collagenase and separate transcriptional profiling of blood, skeletal muscle, and bone marrow. We found that collagenase digestion reduced contamination, but also altered gene expression in the remaining cells. In contrast, in silico filtering of the diaphyseal bone RNA‐seq data for highly expressed blood, skeletal muscle, and bone marrow transcripts significantly increased the correlation between RNA‐seq data from an animal's right and left tibias and from animals with the same Lrp5 genotype. We conclude that reliable and reproducible RNA‐seq data can be obtained from mouse diaphyseal bone and that lack of LRP5 has a more pronounced effect on gene expression than the HBM‐causing LRP5 missense mutation. We identified 84 differentially expressed protein‐coding transcripts between LRP5 "sufficient" (ie, Lrp5+/+ and Lrp5p.A214V/+) and "insufficient" (Lrp5–/–) diaphyseal bone, and far fewer differentially expressed genes between Lrp5p.A214V/+ and Lrp5+/+ diaphyseal bone. © 2013 American Society for Bone and Mineral Research.